2013
DOI: 10.5059/yukigoseikyokaishi.71.1136
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the ^|^ldquo;Cation Pool^|^rdquo; Method

Abstract: Abstract:The cation pool method involves the generation and accumulation of highly reactive organic cations in solution. These can serve as powerful carbon and heteroatom electrophiles in organic synthesis. Recent developments in the cation pool method including the indirect cation pool method, cation chain reactions, and integrated electrochemical chemical reactions are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…Yoshida et al. circumvent formation of the undesired symmetrical biphenyls in an extraordinarily effective way by electrolyzing only one component at low temperature, the second substrate being added subsequently to this cation‐pool;10 when combined efficiently with flow techniques, this ensures control of selectivity 10b. 11 In direct electrolysis, mixtures of HFIP and other protic additives like water or methanol significantly and positively influence the yield and selectivity of anodic phenol–arene cross‐coupling reactions (see Scheme ) 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshida et al. circumvent formation of the undesired symmetrical biphenyls in an extraordinarily effective way by electrolyzing only one component at low temperature, the second substrate being added subsequently to this cation‐pool;10 when combined efficiently with flow techniques, this ensures control of selectivity 10b. 11 In direct electrolysis, mixtures of HFIP and other protic additives like water or methanol significantly and positively influence the yield and selectivity of anodic phenol–arene cross‐coupling reactions (see Scheme ) 7…”
Section: Introductionmentioning
confidence: 99%
“…[10a] Generation of the desired mixed biaryl ab by this strategy is rather difficult. It is statistically underrepresented because the electrochemical potentiali sastrongd riving force for selectivity.Y oshida et al circumventf ormation of the undesired symmetricalb iphenyls in an extraordinarily effective wayb ye lectrolyzingo nly one component at low temperature, the second substrate being added subsequently to this cation-pool; [10] when combinede fficientlyw ith flow techniques, this ensures Scheme1.The products anticipated for direct anodic cross-couplingo f arenes. control of selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…(For recent papers on organic electrosynthesis, see for example, refs [16][17][18] Electrochemical oxidation in solvents normally used in organic syntheses can be carried out by the cation pool method. [19][20][21] We have reported that the electrochemical oxidation of diaryl disulfides (ArSSAr) leads to the formation of ArS(ArSSAr) + , which can be accumulated in solution at low temperatures ( Figure 1). [22][23][24][25][26] This reaction presumably proceeds by generation of "ArS + " followed by its reaction with ArSSAr.…”
Section: Introductionmentioning
confidence: 99%
“…[2] A body of creative work toward this end has been steadily building, including metal-mediated C–H activation chemistry, [3] photochemical methods, [4] and electrochemical oxidation reactions. [5] In particular, the application of electrochemistry in organic synthesis has benefited from advances such as cation pool [6] and flow chemistry techniques, [7] Here, we introduce a simple and inexpensive way of carrying out electrochemical oxidations and demonstrate its utility in diversifying polycyclic lactams.…”
mentioning
confidence: 99%